2019
DOI: 10.17494/ogusbd.548368
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’de Tartışmalı ve Sosyobilimsel Konular Üzerine Yazılan Lisansüstü Tezlerin Eğitim Bilimleri Perspektifinden İncelenmesi

Abstract: This study aims to investigate the dissertations on controversial and socioscientific issues in Turkey between the years 2007 and 2016 in terms of master and doctorate levels, years and departments/disciplines, topics, target groups and research designs of dissertations on controversial and socioscientific issues with regard to the descriptive analysis form prepared by the researcher. The study was designed as a descriptive survey model research. The study revealed that controversial and socioscientific issues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
1
1
0
1
Order By: Relevance
“…Cloning, the theory of evolution, creationist beliefs, natural disasters, and animal rights are the least discussed controversial issues in Turkey. This finding is similar to the results of other studies conducted in Turkey (Avaroğulları, 2015;Çopur, 2015;Seçgin, 2009;Kus, 2015). On the other hand, Walsh's study (1998), conducted in another country, found issues such as creationist beliefs, the theory of evolution, animal rights, disarmament, and multiculturalism to be the most controversial.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Cloning, the theory of evolution, creationist beliefs, natural disasters, and animal rights are the least discussed controversial issues in Turkey. This finding is similar to the results of other studies conducted in Turkey (Avaroğulları, 2015;Çopur, 2015;Seçgin, 2009;Kus, 2015). On the other hand, Walsh's study (1998), conducted in another country, found issues such as creationist beliefs, the theory of evolution, animal rights, disarmament, and multiculturalism to be the most controversial.…”
Section: Resultssupporting
confidence: 92%
“…The quantitative dimension of the study also found that the teachers perceived parental and administrative reactions and the examination-centred education system as problems in teaching controversial issues (Seçgin, 2009;Çopur, 2015). Many other studies (Hess, 2004;Seng & Jaffar, 2014;Zemblas & Kambani, 2012;Philpott, Clabough, McConkey & Tunner, 2011) have also found that teachers face parental and administrative pressures in teaching controversial issues, and that they fear losing their jobs.…”
Section: Resultsmentioning
confidence: 71%
“…Cebesoy & Dönmez Şahin, 2013;Evren Yapıcıoğlu & Kaptan, 2017;Gülhan, 2013;Gürbüzkol & Bakırcı, 2020;Özkul, 2022;Topçu, 2008;Topçu et al, 2011). The related studies are more in science education because socioscientific issues have taken place a concrete place in science education curricula, especially with the 2013 curriculum (Tatar & Adıgüzel, 2019). The studies in the field of social studies education, mostly aimed at determining the perceptions, attitudes and opinions of prospective teachers of social studies and history (Alagöz, 2014;Aynuz, 2020;Baloğlu Uğurlu & Doğan, 2016;Çepni & Geçit, 2020;Seçgin, 2019;Özüdoğru, 2022), teachers (Çopur, 2015;Günal & Kaya, 2016;Öztürk, 2017;Tuncer, 2018), and students (Arslan, 2019;Öztürk, 2022) regarding the controversial issues and the teaching of these topics.…”
Section: Introductionmentioning
confidence: 99%
“…SSI might be international as well as national. On one hand, the ideology dominant in a society and on the other hand the values and beliefs of that particular society are the determinants for what is controversial or not (Tatar and Adıgüzel, 2019).…”
Section: Introductionmentioning
confidence: 99%